Genetic and epigenetic modifications induced by chemotherapeutic drugs: human amniotic fluid stem cells as an in-vitro model - Prabin Upadhyaya; Alessandra Di Serafino; Luca Sorino; Patrizia Ballerini; Marco Marchisio; Laura Pierdomenico; Liborio Stuppia; Ivana Antonucci (BMC, 2019)
Abstract Background Bleomycin, etoposide and cisplatin (BEP) are three chemotherapeutic agents widely used individually or in combination with each other or other chemotherapeutic agents in the treatment of various cancers. These chemotherapeutic agents are cytotoxic; hence, along with killing cancerous cells, they also damage stem cell pools in the body, which causes various negative effects on patients. The epigenetic changes due to the individual action of BEP on stem cells are largely unknown. Methods Human amniotic fluid stem cells (hAFSCs) were treated with our in-vitro standardized dosages of BEP individually, for seven days. The cells were harvested after the treatment and extraction of DNA and RNA were performed. Real-time PCR and flow cytometry were conducted for cell markers analysis. The global DNA methylation was quantified using 5mC specific kit and promoter and CpG methylation % through bisulfite conversion and pyrosequencing. Micro- RNAs (miRNAs) were quantified with real-time qPCR. Results The cytotoxic nature of BEP was observed even at low dosages throughout the experiment. We also investigated the change in the expression of various pluripotent and germline markers and found a significant change in the properties of the cells after the treatments. The methylation of DNA at global, promoter and individual CpG levels largely get fluctuated due to the BEP treatment. Several tested miRNAs showed differential expression. No positive correlation between mRNA and protein expression was observed for some markers. Conclusion Cytotoxic chemotherapeutic agents such as BEP were found to alter stem cell properties of hAFSCs. Different methylation profiles change dynamically, which may explain such changes in cellular properties. Data also suggests that the fate of hAFSCs after treatment may depend upon the interplay between the miRNAs. Finally, our results demonstrate that hAFSCs might prove to be a suitable in-vitro model of stem cells to predict genetic and epigenetic modification due to the action of various drugs.